Unifying Rigid and Soft Bodies Representation: The Sulfur Physics Engine. (28th May 2014) - Maggiorini, Dario; Ripamonti, Laura Anna; Sauro, Federico
Abstract : Video games are (also) real-time interactive graphic simulations: hence, providing a convincing physics simulation for each specific game environment is of paramount importance in the process of achieving a satisfying player experience. While the existing game engines appropriately address many aspects of physics simulation, some others are still in need of improvements. In particular, several specific physics properties of bodies not usually involved in the main game mechanics (e.g., properties useful to represent systems composed by soft bodies), are often poorly rendered by general-purpose engines. This issue may limit game designers when imagining innovative and compelling video games and game mechanics. For this reason, we dug into the problem of appropriately representing soft bodies. Subsequently, we have extended the approach developed for soft bodies to rigid ones, proposing and developing a unified approach in a game engine: Sulfur. To test the engine, we have also designed and developed "Escape from Quaoar, " a prototypal video game whose main game mechanic exploits an elastic rope, and a level editor for the game.